2022
DOI: 10.1590/1516-3180.2021.0288.23072021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and adherence to standard precautions in a hemodialysis unit: a cross-sectional study

Abstract: BACKGROUND: Standard precautions (SPs) are recommended safety measures for healthcare professionals to follow, with a view to preventing healthcare-related infections (HCRIs) and for their own protection. Inadequate adherence to these measures can lead to occurrences of occupational accidents and HCRIs. OBJECTIVES: To ascertain the knowledge of and adherence to SP measures among the nursing staff of a hemodialysis service and the relationship of these variables to occurrences of work accidents with biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…College nurses had higher significant knowledge in general about hemodialysis and about the procedure, while diploma nurse has higher significant knowledge about hemodialysis complication. This findings were parallel with study in Egypt, Sudan and Erbil (15) (8) (16), while in other study in Egypt has shown the year of experiences have significant positive association with the knowledge about hemodialysis but the education level did not show a significant association (12). In this study, more than 5 years' experience also had higher knowledge about hemodialysis but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
“…College nurses had higher significant knowledge in general about hemodialysis and about the procedure, while diploma nurse has higher significant knowledge about hemodialysis complication. This findings were parallel with study in Egypt, Sudan and Erbil (15) (8) (16), while in other study in Egypt has shown the year of experiences have significant positive association with the knowledge about hemodialysis but the education level did not show a significant association (12). In this study, more than 5 years' experience also had higher knowledge about hemodialysis but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 86%